Quantitative parameters of the brain oedema in the dynamics of alcoholic encephalopathy - Shulyatnikova, T. V.; Шулятнікова, Тетяна Володимирівна; Suleimanova, S. V. (Запорізький державний медичний університет, 2019)
Alcoholic encephalopathy, as one of the most frequent and severe complication of the alcoholism, is still of considerable scientific interest, since the fine links of the pathogenesis of this condition remain poorly understood. Particular attention is devoted to characteristics of edematous changes in the brain tissue in chronic course of alcoholic encephalopathy, as well as during its exacerbations in form of acute alcoholic psychosis. The aim of the work is to determine quantitative indicators of oedematous changes in the frontal lobe of deceased patients with alcoholism at different stages to clarify the characteristics of the morphogenesis of alcoholic encephalopathy. Material and methods. It has been studied 60 sectional cases, represented by two groups: 30 cases – the group of the dead with alcoholism І-ІІІ stages (10 cases for І, ІІ and ІІІ subgroups) and 30 cases – for control group. It was studied histopathologically and using morphometry the precentral gyrus cortex of the brain left hemisphere in all cases. Pieces of the brain tissue were fixed in 10% buffered neutral formalin; paraffin sections were stained with hematoxylin-eosin. Morphometric study was run on the material of 30 cases of the group with alcoholism in all stages. Each specimen was studied in 10 standard fields of the Axioscope microscope ("Carl Zeiss", Germany), x20 lens, images were obtained using a DXC-151A video camera ("SONY" – Japan). The counting of quantitative indicators of neurons was carried out in the Videotest-2 computer digital analysis system. Statistical analysis was performed using the licensed program STATISTICA® for Windows 6.0 (StatSoft Inc., No. AXXR712D833214FAN5).
Keywords: тези доповідей